Why are Men more susceptible to COVID-19: A narrative review of current global knowledge - Nematollahi, Shahrzad; Shariatpanahi, Samira; Hosseini, Mohammad Reza; Fatemi, Alireza (Archives of Men's Health, 2020)
Since its inception on December 2019, COVID-19 epidemic now has been titled a global emergency. Rich literature on the global descriptive epidemiology of the cases has shown that the burden of COVID-19 epidemic in terms of both morbidity and mortality is more pronounced among men. Physiological and genetic traits along with numerous differences in social and cultural profile of men are attributed to this discrepancy. This review attempted to delineate various proposed explanations for the observed gender-differences in COVID-19 morbidity and mortality.